2016
DOI: 10.1021/acs.chemmater.6b01796
|View full text |Cite
|
Sign up to set email alerts
|

Missing Piece of the Mechanism of the Turkevich Method: The Critical Role of Citrate Protonation

Abstract: This contribution investigates the growth mechanism of the Turkevich method. The experimental results provide the important missing piece of the mechanistic puzzle which enables the actual control of particle growth in the common Turkevich method. Applying the gained knowledge, the boundary conditions for a successful Turkevich synthesis are deduced. Moreover, the conditions under which the Turkevich method is highly reproducible are derived. Following these conditions, the Turkevich synthesis is modified to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 30 publications
4
79
0
Order By: Relevance
“…Citrate ions are widely utilized in the wet chemical synthesis of silver [3][4][5][6][7][8][9][10][11][12][13][14], gold [15][16][17][18][19][20][21], platinum [22] and other nanoparticles, acting as reducing (direct reduction of aqueous Ag + ions by citrate occurs under boiling or hydrothermal conditions [9][10][11][12][13]), complexing, and stabilizing agent, although the precise mechanisms are far from being fully understood. Сitrate is a key reagent for the preparation of silver nanoplates, cubes, disks, etc., as the selective adsorption of citrate on Ag (111) facets impedes their growth and promotes the yield of anisotropic particles [12,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Citrate ions are widely utilized in the wet chemical synthesis of silver [3][4][5][6][7][8][9][10][11][12][13][14], gold [15][16][17][18][19][20][21], platinum [22] and other nanoparticles, acting as reducing (direct reduction of aqueous Ag + ions by citrate occurs under boiling or hydrothermal conditions [9][10][11][12][13]), complexing, and stabilizing agent, although the precise mechanisms are far from being fully understood. Сitrate is a key reagent for the preparation of silver nanoplates, cubes, disks, etc., as the selective adsorption of citrate on Ag (111) facets impedes their growth and promotes the yield of anisotropic particles [12,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…After the work by Kumar et al [7], authors such as Ji et al [8], Polte et al [9], and Kettemann et al [10] NPs evolve according to the nucleation-aggregation-growth mechanism described, for instance, by Polte et al [9]. These findings prompted us to investigate the model of Kumar et al [7] for different conditions (including different pH values) and verify whether its predictions are accurate or not.…”
Section: Introductionmentioning
confidence: 89%
“…Recent experimental data [10], [13] indicate that the precursor takes two paths: the reduction to form the nuclei and the passivation by . After nucleation, the nuclei aggregate to bigger sizes forming seeds.…”
Section: B Final Ph Of the Mixturementioning
confidence: 99%
“…demonstrated that there is an optimal pH value that gives rise to uniform and monodisperse AuNP. In the same sense, Kettermann et al . studied the Turkevich method in great detail alerting about the influence of the resulting pH of the solution on the size and polydispersion of the obtained AuNP.…”
Section: Introductionmentioning
confidence: 99%